Gaza : Beneath the Bombs - Lock, Sharyn and Irving, Sarah; Afterword By Richard Falk (London Pluto Press, 2010)
The Israeli offensive in Gaza was described by Amnesty international as 22 days of death and destruction. Sharyn Locks eyewitness account brings home the horror of life in Gaza beneath the bombs.
Includes Notes and Index
Keywords: Gaza War (2008-2009) -- Gaza Strip -- Gaza